Land Health Surveillance: An Evidence-Based Approach to Land Ecosystem Management. Illustrated with a Case Study in the West Africa Sahel - United Nations Environment Programme (United Nations Environment Programme, 2012)
Part 1 of this publication presents scientific concepts of land health surveillance and the methods and analytical approaches that are used to make surveillance operational. Part 2 presents a regional application of land health surveillance with a synoptic screening study of land degradation in the Sahel using historical changes in vegetation growth and rainfall patterns, based on remote sensing. Part 3, describes a sampling and measurement framework for field level assessment of land degradation based on a sentinel site surveillance scheme and illustrates its application in Segou Region in Mali. Part 4, draws out the implications of the methods and results for development policy and research and identifies priorities for further development and application of the land health surveillance framework. The final chapter provides succinct recommendations for policy action. The main findings of this report are illustrated in a separate summary for decision makers and further illustrated in Sahel Atlas of Changing Landscapes: Tracing trends and variations in vegetation cover and soil condition.